Nested PCR amplification of the mitochondrial hypervariable region for non-invasive eDNA detection of Cryptobranchus alleganiensis - Patrick Kurtz; Jorge Santo Domingo; Robert Alexander Pyron; David Wendell (PLoS ONE, 2025)
Environmental DNA (eDNA) has proven an invaluable tool in detecting elusive, endangered, or otherwise hard-to-identify species in aquatic ecosystems. The Eastern hellbender salamander (Cryptobranchus alleganiensis) is a fully aquatic amphibian with an increasingly threatened population due to its reliance on exceptional surface water with high levels of dissolved oxygen and low sediment. C. alleganiensis habitat and animal loss has been documented through conservation work, resulting in the U.S. Fish and Wildlife Service recently recommending C. alleganiensis as endangered under the Endangered Species Act. Recent natural disasters in population strongholds have emphasized the need for continued conservation efforts, including reliable, non-invasive methods for monitoring C. alleganiensis populations. Using eDNA extractions from environmental waters, we have developed a nested polymerase chain reaction (PCR) detection strategy targeting the control region of the C. alleganiensis mitochondrial genome. We demonstrate the efficacy of our nested primer set for the detection of Cryptobranchus salamanders in the Ohio River watershed with conventional PCR, quantitative PCR, and digital droplet PCR methods, and rigorously challenge these primers against diverse aquatic amphibian DNA templates found within their habitat using DNA sequencing to confirm the specificity of our target amplicons. Our nested PCR approach overcomes several shortcomings of previous eDNA detection methods for C. alleganiensis, most notably an order of magnitude improvement in the limit of detection for animal DNA in the field.